Weather fluctuations are linked to nesting success and renesting decisions in saffron finches. (16th March 2021) - Marques‐Santos, Fernando; Wischhoff, Uschi; Rodrigues, Marcos
Abstract : Life‐histories of neotropical birds seem to vary beyond what is expected according to patterns from northern temperate regions. This variation is well exemplified by saffron finches Sicalis flaveola in subtropical Brazil. They breed for five months on a climate that is relatively warm and rainy throughout the year. Females may attempt from one nest with two eggs up to three nests with five eggs per season. Previous work showed that age and individual quality were insufficient to explain variation in their breeding traits. Thus, other factors may still influence reproductive traits of investment and productivity in females. We asked 1) whether breeding traits of individual females were related to temperature and rain from previous weeks, and 2) whether fluctuations in weather during nest phases influenced egg and nestling survival. We monitored 237 nests of 70 marked females for four years. We found that the odds of a female starting a subsequent nest increased when temperatures on the preceding 15–6 weeks were low. Nest success decreased alongside the temperatures before laying dates. The odds of eggs surviving until hatching increased when weather was cold and rainy during incubation. There was no correlation between past weather and laying dates, clutch sizes, egg or nestling masses, incubation periods or number of fledglings per nest. The adverse effects of warmer temperatures and the survival benefit of increased rainfall are surprising and contrary to other birds' patterns. The mechanisms that link weather to renesting probability and nest success in saffron finches are still unknown, and we give some suggestions about their nature. We advocate that further studies with this widespread species might provide further insights into the variability of life‐histories in the region.